Use of tobacco and nicotine products among adolescents in Sub-Saharan Africa: protocol for a population-based multi-country household survey - Kisia, Lyagamula; Mohamed, Shukri F.; Kyule, Grace; Tchoupé, Christelle; Abolarin, Olatunbosun; Pokothoane, Retselisitsoe; Gelibo, Terefe; Iddi, Samuel; Okumu, Boscow; Mbaya, Nelson; Kadengye, Damazo T.; Mirindi, Didier M.; et al. (Frontiers in Public Health, 2025)
IntroductionThe use of tobacco among adolescents in low- and middle-income countries is a public health issue of concern. The tobacco industry’s aggressive marketing tactics target young people in African countries, leading to early initiation of tobacco use. While existing evidence focuses on 13-15-year-olds, data from Sub-Saharan Africa indicates that smoking initiation ranges from as young as 7 years old to around 16 years old. The lack of data on adolescent tobacco use in African countries limits policymakers’ ability to implement evidence-based tobacco control policies. This study aims to address the critical lack of quality and timely primary data on adolescent tobacco use, thereby enhancing the country’s capacity to target interventions effectively, engage local governments, and attract global attention and funding for adolescent health initiatives.MethodsWe will conduct a cross-sectional nationwide survey among adolescents aged 10–17 years in urban and rural areas of the Democratic Republic of Congo (DRC), Kenya and Nigeria. This household-based survey will utilize a multi-stage stratified sample design to ensure representation across diverse geographic and demographic characteristics. The sample size calculations resulted in nationally representative samples of 6,701 adolescents in Kenya, 4,803 adolescents in the DRC, and 7,948 adolescents in Nigeria.DiscussionThrough this initiative, we aim to catalyze action at national and international levels to combat the tobacco epidemic among adolescents in Sub Saharan Africa. The findings from the study will empower stakeholders to advocate effective tobacco control measures, promote adolescent health, and safeguard future generations from the harmful effects of tobacco use.